Electron beam emittance measurement at storage ring with internal target - Bashmakov, Yu A.; Korbut, M.S. (Вопросы атомной науки и техники, 2012)
The method for measurement of electron beam axis position and angular beam spread is developed for a storage ring with internal target. The method is based on the usage of elastic scattering of high energy electrons (positrons) circulating in a storage ring on atomic electrons of the target. If the beam has a finite emittance and the azimuth is taken from the beam axis the distribution of the azimuth angle between Bhabha scattering positron and electron has a width proportional to the beam angular spread and a mean value depending on the magnitude of the displacement of the real storage ring close orbit position from ideal one. Monte-Carlo simulation was made for the positron beam with a real angular dispersion for energy range typical for the electron-proton collider HERA. The consideration can be generalize by taking into account the positron beam and the target polarization and final state radiation. This method can be used also at electron-positron and proton-proton colliders.